Identification of Broadleaf Weeds in Citrus: HS-896/HS150, 2/2003 - Futch, Stephen H.; Hall, David W. (EDIS, 2003)
This document is HS-896, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published February 2003. HS-896/HS150: Identification of Broadleaf Weeds in Citrus (ufl.edu)